Five-year measurement data along a 1200 m elevational gradient reveals that global warming increases soil respiration - Takeda, Soichiro; Majima, Ryota; Makita, Naoki; Takahashi, Koichi (Frontiers in Forests and Global Change, 2023)
Soil respiration is a major pathway for CO2 emissions from ecosystems. Owing to its temperature dependency, the soil respiration rate is expected to increase due to global warming, particularly at high elevations. To clarify the effects of soil temperature and volumetric soil water content on soil respiration rates (RS), we examined seasonal changes in RS at five elevations of 1600–2800 m in subalpine coniferous forests in Japan for 5 years. The aboveground biomass of forest stands decreased from 282 to 29 Mg/ha as elevation increased. The monthly mean RS was lower at higher elevations from July to October. While RS was positively correlated with soil temperature at each elevation, the effect of soil water content on RS varied among the five elevations. Seasonal changes in RS could be reproduced from soil temperature and soil water content for each elevation in each year. RS at any temperature was lower at higher elevations because RS was also positively correlated with aboveground biomass. From 1600 to 2800 m, the annual RS was estimated to decrease from 2.79 to 0.74 kg CO2 year–1 m–2. The annual RS along the elevational gradient was predicted to increase by 9–12% and 30–42% under low and high greenhouse gas emission scenarios (annual mean temperature 0.76°C and 3.3°C increases), respectively, during 2095–2100 compared to the current period 2015–2020. Increased soil respiration rate will accelerate global warming via the positive feedback. Overall, our findings suggest that soil respiration evaluation is important not only for calculating the carbon balance of forest stands due to global warming but also for predicting global warming owing to the feedback of CO2 emission from soil to atmosphere.